PERAN E-COMMERCE DAN CLOUD COMPUTING DALAM MENINGKATKAN DAYA SAING USAHA KECIL DAN MENENGAH (UKM) DI INDONESIA - myra andriana (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract Small and medium enterprises (SMEs) have the opportunity to seize the market by implementing e-commerce as an effective marketing medium. E-commerce in SMEs should serve customers well to meet customer needs and provide benefits for SMEs. SMEs face many problems and challenges in their business. Could computing can solve many problems faced by SMEs, especially in terms of cost effectiveness, security, availability and IT resources. Cloud computing is an innovation that can help many aspects of the business because of its practical and economical nature, and allows users to access information anytime and anywhere. This paper describes the benefits of e-commerce applications with cloud computing technology in SMEs. As well as providing an understanding of cloud computing itself, starting from the understanding, characteristics, and cloud computing services. This paper also presents the methodology that will be used to collect data, to see how far computing can have an influence on SME e-commerce technology in Indonesia